Quinazolinone-Directed C–H Activation: A Novel Strategy for the Acetoxylation–Methoxylation of the Arenes - Reddy, B. V. Subba; Narasimhulu, G.; Umadevi, N.; Yadav, J. S. (Synlett, 2012)
2-Aryl-4-quinazolinones undergo smooth acetoxylation in the presence of 5 mol% Pd(OAc)2 and a stoichiometric amount of PhI(OAc)2 via C–H activation to produce the corresponding acetoxy-substituted 4(3H)-quinazolinone derivatives in good yields with high regioselectivity.
Keywords: 2-aryl-4-quinazolinone; hypervalent iodine reagent; acetoxylation; C–H activation